Revitalizing Population Services: Salaman Application in Bandung and E-Lampid in Surabaya Realizing Indonesia's Digital Transformation - Wahyuni, Herpita; Heliana, Heliana (Journal of Governance and Public Affairs, 2025)
This study examines e-government–based population services through the Salaman Application in Bandung and the E-Lampid Application in Surabaya using effectiveness indicators of production, efficiency, satisfaction, adaptation, and development. Using a qualitative approach with NVivo 12 Plus and data from literature and official Twitter accounts (@disdukcapilbdg and @DisdukcapilS), the results show that Salaman outperforms E-Lampid in production (31,861 vs. 18,544 applicants), efficiency (53% vs. 46%), and service development (53% vs. 46%). Service satisfaction is high in both cities, with scores of 86.4–87.95 in Bandung and 89.07 in  Surabaya. In contrast, E-Lampid shows stronger adaptation (54%) compared to Salaman (45%). However, the study is limited to two cities and relies on secondary data, so future research should expand the study area, use primary data, and include variables such as digital literacy and system quality